Faktor Risiko Kejadian Malaria di Puskesmas Cluwak dan Puskesmas Dukuhseti Kabupten Pati - Fadjar Harry Wiwoho; Suharyo Hadisaputro; Ari Suwondo (Jurnal Epidemiologi Kesehatan Komunitas, 2016)
Background: Malaria cases in Indonesia have increased, where the API or the number of malaria positive in a region per thousand population, in 2009 that is 1.85 per 1,000 population rose to 1.96 per 1000 population in 2010. The purpose of this study to determine the risk factors of malaria in Pati Community Health Center.Method: This research used observational research method using case control study and sharpened with qualitative data through indepth interview. The case samples in this study were malaria patients with positive edge blood glucose (+) Plasmodium from case study population subjects, and control study samples were non-exposed to malaria. Data collection was done by observation and interview using questionnaire. The research variables are nutritional status, outdoor habit at night, habit of using mosquito net, habit of using mosquito repellent, presence of house ceiling, condition of wall of house, existence of sewer, existence of  pond  /  fish  pond,  existence  of  bush,  endemic  areas,  and  the  incidence  of  malaria. Processing and data analysis in this study was using Chi Square statistical test and statistical test of Logistic Regression.Results: The results showed that several factors that proved to be a risk factor for malaria occurrence were habit using mosquito net (p value=<0.01); The state of the home sky (p value=0.003); Existence of the gutter around the environment (p value=0.002).Conclusion: Factors that proved to be a risk factor for malaria occurrence were habit using mosquito net; The state of the home sky.